Pengaruh Investment Opportunity Set, Persistensi Laba, Struktur Modal Terhadap Kualitas Laba - Ciellie Christabelle Santoso; Jesica Handoko (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2022)
This study aims to measure the degree of impact of investment opportunities by using the price-to-earnings ratio, measuring persistence by calculating the difference between current period's earnings before tax (EBT) and previous period's profits and then dividing by company assets. Meanwhile, capital structure is measured by dividing the amount of capital by the total debt or debt-to-equity ratio (DER). This study used quantitative methods. Samples are obtained by applying purposive sampling methods, i.e. selecting samples according to various predetermined criteria. The sample for this study is 210 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2018-2020. The result of this study is that there is no effect between the investment opportunity set (IOS) and the quality of the profits obtained. Bottom line, investors don't always use the IOS value parameter when making investment decisions. The quality of a company's profits has a negative impact on the durability of profits. From these results it can be said that if a company has a good level of consistency, it will improve the quality of its profits. Capital structure has a negative impact on profit quality. This means that the higher the value of the company's assets, the lower the quality of the company's profits through debt financing.